Predictors of Health-Related Quality of Life among Buddhist Monks in Phayao Province - ปริยัติ, พระราช; ปริยัติสุธี, พระครูโสภณ; สรกิจ, พระครูพิศาล; สิงห์มณี, ชมพูนุท; เสมอเชื้อ, วโรดม; สุขสถิตย์, เบญจมาศ (Journal of The Royal Thai Army Nurses, 2018)
The objective of this secondary data analysis was to examine predictors of health-related quality of life (HRQOL) among 281 Buddhist monks in Phayao province. Three research instruments were used, including demographic questionnaire, the health behaviors questionnaire, and the SF-36 Thai version. These instruments provided Cronbach’s alpha coefficiency of .76 and .91, respectively. Data were anaylazed by using descriptive statistics and multiple logistic regression. Results showed that 76.16% of monks had good HRQOL. When controlling for age, only health behaviors statistically significantly predicted 11.75% of variances in good HRQOL among monks. For one additional score of health behaviors provided monks 0.93 time of having poor HRQOL (OR 0.93, 95% CI 0.89 – 0.98, p = .0056).